„Köztudomásu dolog ez ott és látták is többen”: Petőfi Sándor „mezőtúri versei” - Boldog-Bernád, István (Studia Litteraria, 2024)
The study examines two articles published simultaneously by Kornél Tábori which contain a detailed description of Sándor Petőfi’s visit to Mezőtúr and record the circumstances of the creation of two poems purportedly written by Petőfi. e research takes an account of contemporary sources to uncover the sequence of events that form the basis of the two articles. While the available data suggests that the texts record fictitious events, they are nevertheless of an academic interest when examined as legends from the perspective of folklore literature. The essay also uncovers the parallels between the legend and the tropes connected to the story recorded by Tábori. Tábori’s two texts are included in the study as appendices.